Assessing the preparedness of WAMZ countries for migration to inflation targeting framework - Olorunsola E. Olowofeso; Maimuna John-Sowe; Ibrahima Diallo; Hissan Abubakari; Dauda Mohammed; Eric Sambolah (West African Monetary Institute (WAMI), 2021)
Inflation targeting (IT) has become the dominant monetary policy framework around the world and most of the countries that have adopted it have successfully improved their monetary policy regime. The objective of this paper is to assess WAMZ member countries' readiness to adopt inflation targeting regime as recommended by the Authority of Heads of State and Government for the single currency program, and to learn from Ghana's experience that have been using the IT framework since 2007. We utilized the prerequisites and initial conditions for IT developed by Miskin (2004) and the IMF (Carare et al., 2002; Freedman et al., 2010) in our assessment of the member countries readiness. Our study revealed the challenges that some WAMZ countries may encounter in adopting the IT framework. For example, while The Gambia would have no major challenges; Guinea needs to improve its monetary policy transmission mechanism; Liberia has major challenges regarding both external and domestic stability as well as monetary policy transmission issues, Nigeria need to continually improve its domestic stability, while Sierra Leone need to focus more on both domestic and external stability. The lesson from Ghana showed that the country has successfully improved its monetary policy transmission mechanism however, experienced challenges including presence of fiscal dominance, weak fiscal positions, and external shocks which impaired its ability to sustainably subdue inflation to the desired level.
Keywords: E52; E58; E31; 330; Monetary policy; Inflation targeting; WAMZ